2022
DOI: 10.1029/2021wr031098
|View full text |Cite
|
Sign up to set email alerts
|

The Resilience of Biofilm‐Bound Sandy Systems to Cyclic Changes in Shear Stress

Abstract: Sand‐attached benthic biofilms drive many important biogeological processes and serve as cooperative “ecosystem engineers”. In aquatic environments, biofilms undergo periodic detachment and re‐colonization due to the regular changes in hydrodynamic forcing. However, legacy impacts of past microbial actions on current biofilm formation and the biostabilization of the substratum sands are yet to be fully understood. In this study, a systematic set of flume experiments were conducted to investigate the effects of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…Biofilms are generally considered to be heterogeneous matrices composed of microbial communities and extracellular polymers (EPS, microbial cell metabolites), which are formed by microbial attachment and growth in natural environments and engineered systems. They stabilize spatial organization mainly by providing intercellular scaffolds formed by EPS [ 83 ], and are therefore essential for stabilizing sediments [ 29 ]. Due to their structural irregularities, biofilms may also have a significant impact on the hydrodynamics of porous media [ 22 ].…”
Section: Results and Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Biofilms are generally considered to be heterogeneous matrices composed of microbial communities and extracellular polymers (EPS, microbial cell metabolites), which are formed by microbial attachment and growth in natural environments and engineered systems. They stabilize spatial organization mainly by providing intercellular scaffolds formed by EPS [ 83 ], and are therefore essential for stabilizing sediments [ 29 ]. Due to their structural irregularities, biofilms may also have a significant impact on the hydrodynamics of porous media [ 22 ].…”
Section: Results and Analysismentioning
confidence: 99%
“…The role of the biofilm as a collector continuously attracts bacteria, further enhancing their deposition [ 23 ]. According to Stoke’s law [ 24 , 27 , 31 ], the settling velocity is proportional to the diameter squared and density of the microbial floc, which shows the importance of biofilm thickness and density in preventing washout [ 24 , 29 , 30 ]. Unfortunately, biofilms degrade over time without a nutrient supply [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of these produce extracellular polymeric substances (EPS) to attach to sand grain surfaces (Gobet et al, 2012;Chen et al, 2017b). The natural rhythmicity of EPS production by diatom has been extensively investigated, which were reported to be well associated with its migration across the sediment-water interface in response to both internal (i.e., the endogenous rhythms) and external factors (i.e, environmental stresses such as hydrodynamic forces and radiation) (de Brouwer and Stal, 2001;Orvain et al, 2003;Perkins et al, 2004;Chen et al, 2022). Direct microscopic observations and technologies have revealed that more than 99.9% of the bacteria live in the form of biofilms on a variety of interfaces (Donlan and Costerton, 2002).…”
Section: Introductionmentioning
confidence: 99%